2020
DOI: 10.3350/cmh.2019.0010n
|View full text |Cite
|
Sign up to set email alerts
|

KASL clinical practice guidelines for liver cirrhosis: Varices, hepatic encephalopathy, and related complications

Abstract: clinical practice. Therefore, these revised guidelines for the treatment of varices and HE are offered for Korean practice to reflect the latest research results and extensive discussions within the revision committee. This guideline contains the opinions of experts and is intended to be a practical reference for the care of patients with varices and HE; it is not an absolute standard of care. The best choices for each patient's care vary from case to case, and the judgment of the doctor in charge is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 386 publications
(473 reference statements)
0
37
0
Order By: Relevance
“…Serum lipid profiles can be altered in patients with chronic liver disease. Some studies have suggested that lipid disorders in patients with liver disease reflect the status of hepatic cellular impairment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Serum lipid profiles can be altered in patients with chronic liver disease. Some studies have suggested that lipid disorders in patients with liver disease reflect the status of hepatic cellular impairment [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PegIFN/RBV or DAA regimens were prescribed according to the practice guideline [ 20 , 21 ] and SVR was defined as undetectable serum HCV-RNA with a lower limit of quantification of 15 IU/mL at 24 or 12 weeks after PegIFN/RBV or DAA regimens, respectively. If histologic information was not available, cirrhosis was clinically defined as follows: (1) platelet count <150,000/μL and ultrasonographic findings suggestive of cirrhosis, including a blunted, nodular liver edge accompanied by splenomegaly (>12 cm); or (2) esophageal or gastric varices [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to epidemiological investigations, the prevalence of HE is approximately 30 to 45%, which is accompanied by an increase in mortality ( Patidar and Bajaj, 2015 ; Xu et al., 2019 ). In the United States, the economic burden of hospitalization for HE amounts to more than $11.9 billion each year ( Hirode et al., 2019 ), which causes significant increases in patient mobility, morbidity, and care utilization ( Jang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%